DETERMINAN RISIKO KEJADIAN ANEMIA PADA REMAJA PUTRI BERDASARKAN JENJANG PENDIDIKAN DI KABUPATEN KEBUMEN - Agustina, Ely Eko; Fridayanti, Warni (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Bleeding as a major cause of high maternal mortality rate inIndonesia begins with anemia.The prevalence of anemia was found different in othercountries.Adolescence is a vulnerable age group to anemic. Anemia in adolescence girlswill have an impact on reproductive health. The purposeof this study to determine the riskof anemia in adolescent girls in Kebumen 2016. This research is an analytic observationalwith case control design.The sample in this study of 120 respondents.The study wasconducted in May-June 2016. Data were collected by questionnaire instruments, SemiQuantitative- Food Frequency Quotionare (SQ-FFQ), height measurement, weighing andlaboratory tests.Data analysis included univariate analysis of the frequency distribution ofresearch variables, bivariate analysis withchi_square test, and multivariate logistic regression analysis. The results showed there was no significant relationship betweenknowledge about anemia and worm infection with the incidence of anemia in adolescentgirls, there is a significant relationship between nutrient intake of energy p = (0.047),protein p = (0.000), iron p = (0.002 ), menstrual pattern p = (0.001) and anthropometricnutritional satus p = (0.021) and the incidence of anemia in adolescent girls. Multivariatelogistic regression analysis showed the most dominant variables on the incidence ofanemia is the nutrient intake of protein in the CI OR 4,255 (1, 850 to 9.784). KebumenDistrict Health Department needs to socialize Nutrition Coaching Educational Institutionsintensively and comprehensively to reduce anemia among adolescents. Socialization andiron supplementation should be done continously with a good evaluation afterimplementation.Keywords: Anemia, Adolescence Girl, Risk of Anemia